Altered Local Brain Amplitude of Fluctuations in Patients With Myotonic Dystrophy Type 1 - Huang, Pei; Luan, Xing-Hua; Xie, Zhou; Li, Meng-Ting; Chen, Sheng-Di; Liu, Jun; Jia, Xi-Ze; Cao, Li; Zhou, Hai-Yan (Frontiers in Aging Neuroscience, 2021)
This study is aimed at investigating the characteristics of the spontaneous brain activity in patients with myotonic dystrophy type 1 (DM1). Eighteen DM1 patients and eighteen healthy controls (HC) were examined by resting-state functional magnetic resonance imaging. Combined methods including amplitude of low-frequency fluctuations (ALFF), fractional amplitude of low-frequency fluctuations (fALFF), and Wavelet transform-based ALFF (Wavelet-ALFF) with standardization, percent amplitude of fluctuation (PerAF) with/without standardization were applied to evaluate the spontaneous brain activity of DM1 patients. Compared to HC, DM1 patients showed decreased ALFF and Wavelet-ALFF in the bilateral precuneus (PCUN), angular gyrus (ANG), inferior parietal, but supramarginal and angular gyri (IPL), posterior cingulate gyrus (PCG), superior frontal gyrus, medial (SFGmed), middle occipital gyrus (MOG), which were mainly distributed in the brain regions of default mode network (DMN). Decreased ALFF and Wavelet-ALFF were also seen in bilateral middle frontal gyrus (MFG), inferior frontal gyrus, opercular part (IFGoperc), which were the main components of executive control network (ECN). DM1 patients also showed decreased fALFF in SFGmed.R, the right anterior cingulate and paracingulate gyri (ACG.R), bilateral MFG. Reduced PerAF in bilateral PCUN, ANG, PCG, MOG, and IPL.L, as well as decreased PerAF without standardization in PCUN.R and bilateral PCG also existed in DM1 patients. In conclusion, DM1 patients had decreased activity in DMN and ECN with increased fluctuations in temporal cortex and cerebellum. Decreased brain activity in DMN were the most repeatable and reliable with PCUN and PCG being the most specific imaging biomarker of brain dysfunction in DM1 patients.